THE MODERN CONCEPT OF MORPHOLOGICAL AND FUNCTIONAL FEATURES OF THE ENDOCRINE GLANDS - Iakushko, O.S. (World of Medicine and Biology, 2016)
Lecture is the important link of submission of theoretical material. Lecture on the endocrine system in the course of histology introduces students to new insights on the morphological and functional features of the endocrine glands and their hormonal activity and the effect on the body. The endocrine system, along with the nervous and immune system, is among the regulatory and integrating systems of the body. It controls the regulation of the body's most important functions: growth, reproduction, proliferation and differentiation of cells, metabolism and energy, secretion, excretion, absorption, and other behavioral reactions. In general, the function of the endocrine system is defined as the maintenance of homeostasis.
Keywords: endocrine glands; hormones